Phylo-biogeographical distribution of whitefly Bemisia tabaci (Insecta: Aleyrodidae) mitotypes in Ecuador - Paredes‐Montero, Jorge R.; Ibarra, María A.; Arias Zambrano, Myriam; Peralta, Esther L.; Brown, Judith K. (Wiley, 2020)
The Bemisia tabaci complex in Ecuador was studied with respect to phylogenetic relationships and eco‐geographical distribution. Whitefly samples were collected from natural and agricultural environments in nine provinces of Ecuador (latitude, 2° N–5° S; longitude, 78°–81° W). Mitotypes were identified based on phylogenetic analysis of the 3′‐mtCOI‐tRNAleu region (832 bp) and corrected pairwise distance analysis. The distribution of mitotypes was modeled using MaxEnt, and their predicted niches were characterized according to environmental gradients. Four B. tabaci mitotypes were identified, of which three are endemic, herein ECU1–3, and the other is the introduced B mitotype. Mitotypes ECU1 (44%), ECU2 (0.74%), and ECU3 (1.47%) grouped in the American Tropics (AMTROP) species and diverged by as much as 10%, which was higher than previous estimates for the AMTROP clade of 7–8.6%. Although haplotypes of ECU1 and ECU2 are known from the American Tropics, this is the first report of the ECU3 mitotype, which may possibly be restricted to southern Ecuador. The distribution of the three ECU‐endemic mitotypes spanned the high‐altitude niches of the western slope of the Andes, rich in microclimates with variable temperature and humidity conditions. The non‐endemic B mitotype (47%) occurred only in the irrigated cropping systems located in hot and/or dry‐tropical ecological niches. Of the endemic mitotypes, ECU1 occupied the most ecological niches. Among variables contributing to ECU1 and B mitotype niche range assignments, the most significant to influence ecological range was rainfall. The B. tabaci endemic to Ecuador were more diverse with respect to mtCOI‐tRNAleu sequence than previously known, and occupied distinct microclimate niches suggestive of ecological resilience